Psychogeography as Social Activism in Katerina Cizek’s Digital Documentaries Highrise, The 1000th Tower and Out My Window - Siobhan O’Flynn (Revue LISA)
With the rapid emergence of new digital technologies and social media platforms, documentary filmmaking is undergoing significant shifts globally and the works of Canada’s NFB Interactive program are at the forefront of innovation in the international sphere. By experimenting with new forms, Katerina Cizek’s interactive documentaries, Filmmaker-In-Residence, and the multi-year, many-media project Highrise have revitalized the participatory production process pioneered in the 1970s by the NFB, using “Interventionist Media” to empower marginalized communities and effect social change. In positioning traditional documentary subjects as collaborators, Cizek’s work challenges existing social models and dominant or media representations of at-risk and low-income communities, creating platforms for individuals to tell their stories as counters to official constructions of these often underrepresented neighbourhoods. In doing so, Cizek’s interactive documentaries lay a claim to what David Harvey has termed “the rights to the city” of all inhabitants. And although the use of digital technologies raises questions as to access and equity in the digital divide, her projects address this tension directly often working with government and community members to effect change in urban policy and planning. This essay examines how these works rewrite History within the context of the Social Web as an ongoing participatory narrative.